Towards pro-poor and voluntary PES: assessment of willingness to pay and willingness to accept PES contract in central Vietnam. Issue 1 (2nd January 2022) - Do, Trong Hoan; Patton, Ivanna; Catacutan, Delia
ABSTRACT: This study employed Contingent Valuation and Discrete Choice Experiment methods to investigate the potential of a Payment for Ecosystem Service mechanism that incentivizes sustainable land use practices by determining the willingness of ecosystem service beneficiaries to pay for delivery of services via adoption of sustainable land use practices by upland poor, ethnic minority communities, and vice versa, the willingness of communities to adopt such practices upstream of Vu Gia river, central Vietnam. From the users' side, 64% and 56% of pooled respondents said they are willing to pay a higher rate for water and electricity consumption, respectively, if upstream watershed management is improved. On the providers' side, WTA was high if the conditionality is relaxed. Our findings suggest a fundamental challenge in designing PES that matches the needs of buyers and providers – a scheme that ensures ecosystem service flows but does not impose stringent rules that limit stakeholders' participation.